Pengembangan Media Layanan Bimbingan Klasikal Berbasis TikTok tentang Pentingnya Self-Love dan Cara Menerapkannya dalam Diri Remaja - Shelly Maylinda; Hadi Pranoto; Eko Susanto (Counseling Milenial (CM), 2025)
The purpose of this research is to develop a TikTok-based classical guidance service media on the importance of self-love and how to apply it to adolescents. This research model is based on the development model by Dick and Carry (1996), with a modified development plan consisting of four stages: analysis, design, development, and implementation. Based on the research results, product development in the form of TikTok video content showed a positive response with feasibility results of "Very Feasible" for all indicators. From the data obtained it can be concluded that the delivery of material, design and discussion is clear, the media is designed attractively, the use of media can increase understanding and this media is useful in classical guidance service activities.